Socialization of Waqf, Zakat, and Infaq Management Model for University - Nurdin, Ridwan; Dahlan, Haris Bin; Othman, Razali Bin; Nizam, Ahmad; Novindra, Novindra; Hanidah, In In; Rivani, Rivani; Nisva, Raisa Ullya (Jurnal Pengabdian Bakti Akademisi, 2025)
This community service activity aimed to enhance the understanding of waqf, zakat, and infaq (WZI) management among students and lecturers of the Faculty of Economics and Business, Universitas Syiah Kuala. The activity was carried out in collaboration with Center for WAZAN University Putra Malaysia and several academic partners. The core issue addressed was the lack of integrated knowledge and practical insight into the management of Islamic social funds, which are vital in achieving social justice and poverty alleviation. Using the service learning method, the activity combined direct instruction, reflection, and interactive discussion with expert facilitators. The event took place at Center for WAZAN UPM on January 14, 2025, involving 10 participants. Results showed a significant increase in participants understanding, as demonstrated by a 46% improvement between pre-test and post-test scores. This indicates the effectiveness of collaborative and contextual approaches in strengthening WZI literacy and contributes to the achievement of Sustainable Development Goals (SDGs), particularly in quality education and poverty reduction.